Synthesis of gelatin stabilized gold nanoparticles with seed particles enlargement by gamma Co-60 irradiation - Duy, Nguyen Ngoc; Thu Thao, Doan Thi; Dong Quy, Hoang Thi; Phu, Dang Van; Du, Bui Duy; Hien, nguyen Quoc (Vietnam Journal of Chemistry, 2017)
Gold nanoparticles (AuNPs) with size from 13 to ~36 nm were synthesized by γ-irradiation method using gelatin as stabilizer. The AuNPs with controllable size were prepared using various concentration of Au3+ from 0.5 to 2 mM and seed particle enlargement with different ratios of [Au3+]/[Auo] up to 50. Maximum absorption wavelength (λmax) was measured by UV-Vis spectroscopy, and particle size was determined from TEM images. Results showed that the size of AuNPs increased with the Au3+ concentration. The seed enlargement approach is efficient to control the size of AuNPs. The value of λmax shifted from 527.5 nm (seed particles) to 537.5 nm, and the size of AuNPs increased from 13 nm (seed particles) to ~36 nm for concentration ratio of [Au3+]/[Auo] up to 40. Thus, γ-irradiation method is favorable for production of AuNPs with controllable size and high purity. The AuNPs/gelatin synthesized by γ-irradiation with the advantages of environmental friendly and mass production process may be potentially promising for applications in medicines, cosmetics and in other fields as well. Keywords. Gold, Nanoparticles, Gelatin, γ-irradiation.